Uncover Intermestic: Covid-19 Vaccination Implementation Policy In West Sumatra - Inda Mustika Permata (Cenderawasih University, 2023)
West Sumatra is one of the provinces in Indonesia where most of the people are of the Minangkabau ethnicity. People in the province base their lives on the customs and religion of Islam. As of October 2021, West Sumatra had not performed well in terms of vaccination rates. It was one of the two provinces in Indonesia with the lowest acceptance rate of the COVID-19 vaccine at the time. The government of West Sumatra did not sanction vaccine refusal either. This resulted in a slowdown in the government’s objective of creating herd immunity. This article, therefore, aims to analyze the local values of West Sumatra, which can be utilized as a means of overcoming this situation. The research method used in this study was qualitative, with primary data collected through interviews, and secondary data obtained from journals, books, reports, and news articles. The result shows that the Covid-19 is a global problem which requires a domestic response by involving local actors from social capital networks in West Sumatra.KEYWORDSCovid-19; Intermestic; Policy; West Sumatra